Recurrent Venous Thrombosis in a Hypofibrinogenemic Patient Despite a Heterozygous Deletion of the Fibrinogen Gene Cluster and Hemizygous FGB p.Pro265Leu Variant Mimicking a Homozygous Genotype - Punniyamoorthy, Sutharshini; Leinøe, Eva Birgitte; Jensen, Esther Agnete; Bartels, Emil Daniel; Pedersen, Inge Søkilde; Bor, Mustafa Vakur (Hämostaseologie, 2025)
Hypofibrinogenemia is a congenital fibrinogen disorder characterized by a proportional decrease of functional and antigenic fibrinogen levels. Herein, we present a unique case illustrating the complex genotype–phenotype relationship in hypofibrinogenemia and the inability of low fibrinogen levels to counteract hypercoagulability.A 77-year-old male with factor V Leiden heterozygosity experienced surgery-related deep vein thrombosis at ages 65 and 71, along with poor wound healing and postoperative hematomas. Proportionally reduced functional and antigenic fibrinogen levels revealed hypofibrinogenemia. Whole exome sequencing identified a heterozygous fibrinogen gene cluster deletion and a hemizygous variant (p.Pro265Leu, rs6054) in the fibrinogen β (FGB) gene, both of which are associated with hypofibrinogenemia. The youngest son, who has noticeably higher fibrinogen levels, shares the deletion but does not carry the hemizygous FGB variant. This suggests that the FGB variant (p.Pro265Leu) contributes to a greater reduction in fibrinogen levels.This case suggests that the coexistence of thrombotic risk factors and potentially reduced thrombin clearance—resulting from low fibrinogen levels due to a fibrinogen gene cluster deletion and a hemizygous FGB variant—may shift the hemostatic balance toward thrombosis in a patient with moderate hypofibrinogenemia.
Keywords: fibrinogen; hypofibrinogenemia; variant; deletion; thrombosis